2012
DOI: 10.1371/journal.pone.0046682
|View full text |Cite
|
Sign up to set email alerts
|

LH and hCG Action on the Same Receptor Results in Quantitatively and Qualitatively Different Intracellular Signalling

Abstract: Human luteinizing hormone (hLH) and chorionic gonadotropin (hCG) act on the same receptor (LHCGR) but it is not known whether they elicit the same cellular and molecular response. This study compares for the first time the activation of cell-signalling pathways and gene expression in response to hLH and hCG. Using recombinant hLH and recombinant hCG we evaluated the kinetics of cAMP production in COS-7 and hGL5 cells permanently expressing LHCGR (COS-7/LHCGR, hGL5/LHCGR), as well as cAMP, ERK1/2, AKT activatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
195
1
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 229 publications
(219 citation statements)
references
References 88 publications
13
195
1
2
Order By: Relevance
“…PKA also mediates the activation of the cAMP-response element-binding protein (CREB), modulating the expression of target genes, such as the steroidogenic acute regulatory protein ( STARD1 ) gene, and testosterone production. Previous studies demonstrated different interactions between the gonadotropins and their common receptor [1417], as well as specific intracellular signaling and downstream events in goat and human granulosa lutein cells in vitro [1820]. Especially, hCG has higher cAMP-mediated steroidogenic and pro-apoptotic potential than LH, which, in turn is more effective in activating anti-apoptotic and proliferative events via ERK1/2 and AKT-pathways in vitro, while similar kinetics of intracellular cAMP reversibility were found in mouse Leydig tumor cells (MLTC-1) stimulated by the two human gonadotropins [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PKA also mediates the activation of the cAMP-response element-binding protein (CREB), modulating the expression of target genes, such as the steroidogenic acute regulatory protein ( STARD1 ) gene, and testosterone production. Previous studies demonstrated different interactions between the gonadotropins and their common receptor [1417], as well as specific intracellular signaling and downstream events in goat and human granulosa lutein cells in vitro [1820]. Especially, hCG has higher cAMP-mediated steroidogenic and pro-apoptotic potential than LH, which, in turn is more effective in activating anti-apoptotic and proliferative events via ERK1/2 and AKT-pathways in vitro, while similar kinetics of intracellular cAMP reversibility were found in mouse Leydig tumor cells (MLTC-1) stimulated by the two human gonadotropins [21].…”
Section: Introductionmentioning
confidence: 99%
“…the methods for unit assignment to gonadotropins used for pharmacological treatment in humans. Human LH receptor mediates both quantitatively and qualitatively LH- and hCG-dependent signals in human primary granulosa cells [18, 19], revealing that LHCGR discriminates hormone-specific events. Therefore, we challenge the concept that gonadotropins’ activity can be properly characterized by the assessment of testosterone-dependent endpoints.…”
Section: Introductionmentioning
confidence: 99%
“…Testicular steroidogenesis can be stimulated by LH and hCG, sharing the same LH/choriogonadotropin receptor (LHCGR). However, hCG has higher in vitro activity than LH in terms of cAMP production (28). Moreover, Park and coworkers have recently demonstrated that hCG induces steroidogenic enzyme in vivo in male mice and in vitro in mouse Leydig tumor cells (mLTC-1) (29).…”
Section: Discussionmentioning
confidence: 99%
“…This result has to be carefully considered, because E2 is measured using immunoassay and not LC-MS/MS. The quick response of E2 to hCG reflects the rapid stimulation of CYP19 expression by this gonadotropin in the target cell (28). However, lower serum concentrations of E2 in KS than in controls probably depend on the higher TS levels in eugonadal men, because aromatization is more efficient in KS subjects, as suggested by the significantly higher E2/TS ratios.…”
Section: Discussionmentioning
confidence: 99%
“…The FDA approved the use of about 30 of them and more than 200 others are currently under clinical trials. 24,25 They bind monospecifically to the cell surface antigens of cancer and other cells and trigger the events that culminate in their death. 26,27 The immunotherapies against cancers and some autoimmune diseases with mAbs are rapidly gaining ground.…”
Section: Inclusion Of Hcg In the Family Of Therapeutic Glycoproteinsmentioning
confidence: 99%